Drugs, deviancy and democracy in Iran: the interaction of state and civil society - Christensen, Janne Bjerre (International library of Iranian studies)
Explores the mounting problems of drug use in Iran, how treatment became legalized in 1998, how local NGOs offer methadone treatment in Tehran and face continuous political challenges in doing so, and how drug use is critically discussed in Iranian media and cinema.--From publisher description